2019
DOI: 10.4103/joacp.joacp_350_17
|View full text |Cite
|
Sign up to set email alerts
|

Incidence and predictors of postoperative pulmonary complications in patients undergoing craniotomy and excision of posterior fossa tumor

Abstract: Background and Aims: Infratentorial neurosurgical procedures are considered high risk for the development of postoperative pulmonary complications (POPCs), prolonging hospital stay of patients with substantial morbidity and mortality. Material and Methods: Patients between the ages of 18 and 65 years, who underwent elective surgery for posterior fossa tumors over a period of two years, were reviewed. Data including American Society of Anesthesiologists physical status; … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
7
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(10 citation statements)
references
References 24 publications
2
7
1
Order By: Relevance
“…Possibly, the early screening for dysphagia and the stringent use of FEES to determine nutrition and therapeutic management might explain the low rate of post-OP pneumonia (n = 1) in our cohort. In contrast to previous studies, we also did not observe any significant differences regarding the length of hospital stay between dysphagic and non-dysphagic patients [4,7,11,22,23].…”
Section: Discussioncontrasting
confidence: 99%
See 2 more Smart Citations
“…Possibly, the early screening for dysphagia and the stringent use of FEES to determine nutrition and therapeutic management might explain the low rate of post-OP pneumonia (n = 1) in our cohort. In contrast to previous studies, we also did not observe any significant differences regarding the length of hospital stay between dysphagic and non-dysphagic patients [4,7,11,22,23].…”
Section: Discussioncontrasting
confidence: 99%
“…Additionally, premature spillage as a result of delayed pharyngeal swallow could be observed just as often. Post-surgical brainstem edema and/or brainstem disturbance impacting the forward signal from the swallowing centers to cranial nerves might be discussed as a potential underlying cause of the latter finding [7].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous study identified increasing operative time, increasing age, and increasing estimated blood loss, diabetes, chronic obstructive pulmonary disease, preoperative leukocytosis, American Society of Anesthesiologists classification ≥ 3, and infratentorial lesions as risk factors for postoperative pneumonia in postcraniotomy patients 17 19 . However, in infratentorial craniotomy with high risk for the development of postoperative pulmonary complications, the predictors for the occurrence of postoperative pulmonary complications were postoperative blood transfusion, lower cranial nerve palsy, prolonged ICU stay and tracheostomy 20 . Our result showed that pulmonary imaging abnormalities on the first postoperative chest CT image was more frequently incident in patients with hypoalbuminemia than in patients without hypoalbuminemia, with the incidence of 39.2%.…”
Section: Discussionmentioning
confidence: 99%
“…Previous study identi ed increasing operative time, increasing age, and increasing estimated blood loss, diabetes, chronic obstructive pulmonary disease, preoperative leukocytosis, American Society of Anesthesiologists classi cation ≥ 3, and infratentorial lesions as risk factors for postoperative pneumonia in postcraniotomy patients [15][16][17] . However, in infratentorial craniotomy with high risk for the development of postoperative pulmonary complications, the predictors for the occurrence of postoperative pulmonary complications were postoperative blood transfusion, lower cranial nerve palsy, prolonged ICU stay and tracheostomy 18 . Our result showed that pneumonia was more frequently incident in patients with hypoalbuminemia than in patients without hypoalbuminemia.…”
Section: Discussionmentioning
confidence: 99%